Solubility and Crystallizability: Facile Access to Functionalized π‐Conjugated Compounds with Chlorendylimide Protecting Groups. Issue 4 (26th November 2014) - Gebers, Jan; Rolland, Damien; Marty, Roman; Suàrez, Stéphane; Cervini, Luca; Scopelliti, Rosario; Brauer, Jan Cornelius; Frauenrath, Holger
Abstract Functional π‐conjugated molecules are relevant for the preparation of new organic electronic materials with improved performance. However, their synthesis is often rendered difficult by their inherently low solubility, and the permanent attachment of solubilizing groups may change the properties of the material. Here, we introduced the chlorendylimidyl moiety as a new temporary protecting group for the straightforward large‐scale synthesis of protected quarter‐, sexi‐, octathiophene, and perylene bisimide diamine and dicarboxylic acid derivatives. The obtained chlorendylimides and chlorendylimidyl active esters were highly soluble in organic solvents, and optical spectroscopy confirmed the low tendency of the compounds to aggregate in solution. At the same time, they could be conveniently purified by recrystallization or precipitation. Single‐crystal X‐ray structures obtained for most compounds showed supramolecular motifs highlighting the role of the rigid, polychlorinated chlorendyl moieties in their crystallization. The obtained protected diamine and dicarboxylic acid derivatives were easily deprotected and converted into various amide‐substituted oligothiophenes and perylene bisimides that are of interest as new functional materials for organic electronic thin film or nanowire devices.